A Comparative Analysis of Two Creative Metal Sculptors: Adeola Balogun and Dotun Popoola - Adeyemi, Adedola Olayinka; Azeez, Azeezat Adeola; Essien, Dorcas Rich; Ikwueme, Faith Obianuju (NIU Journal of Social Sciences, 2024)
Welded metal sculpture has gained significant recognition within the art world. It is exhibited in prestigious galleries, museums, and public spaces globally. This article presents a comparative analysis of two renowned welded metal sculptors, Adeola Balogun and Dotun Popoola examining their artistic styles, techniques, and thematic representations. Research has been carried out on these two artists but the comparative analysis of their works is yet to be documented hence this study. By exploring the work of these artists, the article aims to provide insights into the diverse approaches employed in the field of welded metal sculpture. The analysis is supported by critical evaluation of relevant sources including scholarly articles, books, and gallery exhibitions, to highlight the distinctive characteristics and contributions of each artist. Keywords: Welded metal, sculpture comparative analysis,